Increased risk of respiratory viral infections in elite athletes: A controlled study - Valtonen, M.; Grönroos, W.; Luoto, R.; Waris, M.; Uhari, M.; Heinonen, O. J.; Ruuskanen, O. (PLOS ONE, 2021)
Background: Respiratory symptoms are commonly recognised in elite athletes. The occurrence, etiology and clinical presentation of the illnesses in athletes is unclear. Methods: We performed a prospective controlled study of respiratory viral infections in Team Finland during Nordic World Ski Championships 2019. There were 26 athletes and 36 staff members. Nasal swabs were taken at the onset of a symptom and on days 1, 7, and 13 during the follow-up of 14 days. Respiratory viruses were searched for by 3 different molecular multiplex tests. Fifty-two matched control subjects were studied in Finland during the same period. Results: Ten out of 26 (38%) athletes, 6 out of 36 (17%) staff, and 3 out of 52 (6%) control subjects experienced symptoms of respiratory infection (p = 0.0013). The relative risks for acquiring symptomatic infection were 6.7 (95% confidence interval [CI], 2.1-21.0) of athletes and 2.9 (95% CI, 0.84-10.0) of the staff as compared to the controls. Asymptomatic infections were identified in 8%, 22%, and 19%, respectively (p = 0.30). The etiology of respiratory infections was detected in 84% of the cases. Conclusion: The athletes had a 7-fold increase in the risk of illness compared to normally exercising control subjects.